MALARIA PARASITAEMIA AMONG BLOOD DONORS IN ILORIN, NIGERIA. - Olawumi, Hannah Oluwayemisi; Fadeyi, Abayomi; Babatunde, Shola K; Akanbi II, Aliu A; Babatunde, Abiola S; Sani, Musa A; Aderibigbe, Sunday A (African Journal of Infectious Diseases (AJID), 2014)
Background: The prevalence of malaria parasitaemia among blood donors in Ilorin has not been documented. In this study, we determined the prevalence of malaria parasitaemia among blood donors in Ilorin, as well as, the sociodemographic and other factors associated with it. Method: This was a hospital- based cross sectional study involving 308 consenting blood donors. The sociodemographic characteristics of participants as well as blood donation history were obtained using structured questionnaires specifically designed for this purpose. Giemsa-stained thick and thin blood films to identify malaria parasites were performed using standard method. ABO blood grouping and haemoglobin electrophoresis tests were also done using standard methods. Results: The prevalence of malaria parasitaemia among blood donors in Ilorin was 27.3%. The parasite species found were more of Plasmodium falciparum(85.7%) than Plasmodium malariae(14.3%) . There was no age or sex difference in malaria parasitaemia. (p-value of 0.8 and 0.32 respectively). A greater proportion of blood group O individuals had malaria parasitaemia than groups A and B but this difference was not significant (p-value = 0.13). There was also no significant difference among haemoglobin genotypes. Conclusion: The prevalence of malaria parasites among blood donors in Ilorin is considerably high and lack of routine screening of blood puts recipients at risk. We recommend that routine screening for malaria parasites be commenced in our blood banks. Treatment of donor blood with riboflavin and UV light to inactivate malaria parasites and other infectious pathogens before they are transfused to patients may also be considered in our blood banks.